AN ECONOMIC ANALYSIS OF RAISING FUEL PRICE IN INDONESIA - Catur Sugiyanto (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
This paper outlines economic frameworks for analyzing the impact of increasing Juel price on the Indonesian economy. The discussions focus on the analysis of inter-fuels substitution, impact of raising fuel price on cost of productions and on the air quality, and the potential benefits-costs from the mentioned policy. The responsiveness of emission with respect to fuel prices makes fuel prices a powerful tool in the kit of indirect policy instruments available to the policy maker.Several empirical researches show that Juel price can be formulated to induce inter-fuel substitution to reduce the pollution and not necessarily induce high inflation. However, increase in prices for pollution-laden fuels will generally lead to demand reduction, and the net effect on emission will depend on: whether other fuels will produce lesser pollutant, their cross price elasticities are positive, and which fuel share in the total input used are high (the higher the share of fuel the lesser the price elasticity - need higher percentage change in price to decrease the use of such fuel).The impacts of fuel price policy on the Indonesian government budget is examined through change in the government revenue, both from the direct revenue of oils and natural gas sectors and taxation. Lastly, the fuel price policy could be directed to increase the air quality which beneficial for human being.